Analysis of Transportation Planning, Organizing, Actuating, and Controlling Management of Trans Metro Pasundan Bandung Raya - Muhammad Faisal Haq; Deritama Ramadhani Salampessy; Selfa Aulia (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Kuningan, 2026)
The growth of private vehicles in Greater Bandung, which will reach 2.2 million units by 2023, has made the region one of the most congested cities in Asia. The West Java Provincial Government responded to this problem by launching the Trans Metro Pasundan (TMP) program as Bus Rapid Transit (BRT)-based mass transportation through the Buy The Service (BTS) scheme. This study aims to analyze the effectiveness of TMP management using the POAC (Planning, Organizing, Actuating, Controlling) framework and review the application of planning ethics which includes procedural, communicative, environmental, economic, and social aspects. The research method used is qualitative with content analysis supported by the Social Impact Assessment (SIA) framework. The results show that although the TMP has been designed with a clear master plan, modern facilities, and affordable fares, the occupancy rate is still low (0.33%) due to limited socialization, minimal routes (only 5 corridors), subsidy dependency, and resistance from other modes of transportation. Institutional and political barriers such as cross-regional coordination, cross-period policy inconsistencies, and conflicts of interest with conventional transportation exacerbate the situation. Therefore, the success of TMP in realizing effective and sustainable public transportation depends heavily on policy consistency, route expansion, strengthening governance, and increasing public participation.